Analisis Pengungkapan ESG terhadap Profitabilitas dengan Kapitalisasi Pasar sebagai Variabel Moderasi - Hadi Setyo Nugroho (Jurnal Akuntansi, Manajemen dan Ekonomi, 2026)
The study examines the effect of Environmental, Social, and Governance (ESG) disclosure on profitability measured by Return on Equity (ROE), with market capitalization as a moderating variable and leverage (DER) as a control variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024, using 164 firm-year observations. ESG disclosure is measured using a Global Reporting Initiative (GRI)-based checklist, while profitability, firm size, and leverage are measured using standard financial ratios. The results of multiple linear regression show that all three ESG dimensions Environmental Disclosure, Social Disclosure, and Governance Disclosure have a positive and significant effect on ROE, indicating that transparent sustainability reporting contributes to higher profitability. However, the moderation test reveals that market capitalization does not strengthen the relationship between ESG disclosure and profitability, suggesting that firm size does not influence the ability of companies to convert ESG practices into financial gains. These findings highlight the strategic importance of ESG disclosure for firm performance in the Indonesian energy sector while emphasizing that firm size does not alter this relationship.